Padrões e mecanismos estruturadores da diversidade taxonômica e funcional de comunidades de formigas na Cadeia do Espinhaço - Flávio Siqueira de Castro (2019)
Mountains are considered ideal models for the study of patterns and understanding of the processes that determine species distribution in space-time., Exhibit extreme environmental conditions for biodiversity distribution, presenting restricted communities and high taxonomic and functional diversity of species. In this sense, I use the ants found in the mountains of the Espinhaço Range as objects of study. The thesis is divided into two chapters. The goal is to determine the taxonomic and functional patterns and structuring mechanisms of the Formicidae communities in spatiotemporal gradients along the Espinhaço Range, at different spatial scales. In addition, to elucidate biogeographic aspects of these communities in rupestrian field and evaluate how ant communities respond to different environmental variables. In the first chapter, we investigated patterns of taxonomic and functional diversity (α and β diversity) of ants in a mountainous landscape of the Espinhaço Range (Serra do Cipó) and the mechanisms associated with these patterns in different spatio-temporal dimensions. In the second chapter, we evaluated patterns of functional diversity of ant communities and individual species attributes (colour and body size) in an extensive rupestrian field sampling over 12 mountains at different elevations in the Espinhaço Range. We verified the effects of environmental variables on the functional structure of ant community diversity and individual species attributes in ancient mountains. Three macroecological hypotheses associated with clinal tegument colour variation were tested to verify the role of tegument colour and body size variation in a tropical geoclimatic gradient of elevation and latitude. We found that elevation variation and the effects of elevation gradient geoclimatic variables are more important in structuring the taxonomic and functional diversity of ants than latitudinal variation and the effects of their geoclimatic variables.